Bycatch in local fishery disrupts natural reestablishment of Eurasian otter in western Norway. Issue 7 (22nd April 2020) - Landa, Arild; Guidos, Steven
Abstract: Lack of proper estimates of nonreported bycatch has made it difficult to evaluate the actual impact of bycatch in many local fisheries. For the Eurasian otter ( Lutra lutra ), there are no published estimates on the extent to which bycatch is unreported, despite nonreporting being a well‐known issue. Through public outreach efforts in local news and media we collected information from citizen scientists on nonreported otter mortalities of a small‐scale fishery in western Norway along the recent natural expansion front of otters. We compared this to deaths that were properly registered by local authorities. In total, cause of mortality was determined from 218 otters between 2003 and 2018. We found that the chances of a mortality being properly reported varied between type of death. Drowning in fyke and gillnets were the most common cause of mortality, and at least 61 and 69% of these deaths were never reported, respectively. The high level of bycatch occurring in the otters' current region of expansion is likely to have demographic impacts and hinder otter reestablishment in the area. Banning the use of fyke nets and setting a minimum fishing depth for gillnets would enhance otter recovery and simultaneously alleviate bycatch of other nontarget species in the region, while having little economic impact on a fishery which is mostly noncommercial. The case of the otter is a classic example of lack of communication between government agencies which have so far failed to establish platforms where issues like this can be discussed and solved by adequate law implementation.